Entre la docencia y la academia La modernización de la Universidad de San Marcos, 1860-1928 - Loayza, Alex (2008)
This article presents a general vision of the history of the university of San Marcos and exposes the institutional mechanisms across which it was granting academic degrees to the graduating students in fulfillment of a set of educational intentions raised between 1860 and 1928. The aim of the text is to reconstruct the role that fulfills the university in the society in a historical conjuncture and to revise the negative image left by the generations of Nine hundred and of the Centenary. Finally, it postulates a few brief reflections on the value of the graduation theses as historical documents and the use of contemporary historiography.